Evaluation of honey authenticity in Lebanon by analysis of carbon stable isotope ratio using elemental analyzer and liquid chromatography coupled to isotope ratio mass spectrometry. (17th May 2021) - El Hawari, Khaled; Al Iskandarani, Mohamad; Jaber, Farouk; Ezzeddine, Raed; Ziller, Luca; Perini, Matteo; Bontempo, Luana; Pellegrini, Maura; Camin, Federica
Abstract: Honey is one of the most valuable sweeteners consumed by humans all over the world. Consequently, it is often a target for adulteration through the addition of different sugar syrups during or after honey production, resulting in a reduction in its nutritive value. For the first time, this study analyzes honey samples of various botanical species collected from different Lebanese regions using element analyzer (EA) and liquid chromatography (LC) coupled with isotope ratio mass spectrometry (IRMS). The δ 13 C of bulk honey, its protein fraction, and the main individual sugars (glucose, fructose, disaccharides, and trisaccharide) were determined, in order to characterize and evaluate the authenticity of honey consumed in Lebanon. The results showed that the δ 13 C values for bulk honey and its protein range from −26.5‰ to −24.5‰ and from −26.4‰ to −24.7‰, respectively, for authentic samples. δ 13 C values for samples adulterated with sugar syrups range from −11.2‰ to −25.1‰ for bulk honey and from −26.6‰ to −23.7‰ for its proteins, with a difference between bulk and protein values between −1 and −8.7‰. Using LC‐C‐IRMS techniques, the δ 13 C of individual sugars provides additional information on the presence of undeclared sugars. We found that all authentic samples had Δδ 13 Cf‐g and Δδ 13 C max values within the naturally occurring range of ±1‰ and ±2.1‰, respectively, while the adulterated samples fall outside the Δδ 13 C ranges. The oligosaccharide peak was detected in most adulterated samples.